The Influence of Existential Authenticity and Experience Quality on Visitor Loyalty with Trust Moderation in Indonesian Music Festivals - Ayuba Danelyza Mardhatillah; Effed Darta Hadi; Lizar Alfansi; Chairil Afandy (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Music festivals have become increasingly important in experience-based tourism activities. This study examines the influence of existential authenticity and experience quality on visitor loyalty in Indonesian music festivals, with experience quality serving as a mediating variable and trust acting as a moderating variable. Data from 282 respondents who have attended Indonesian music festivals were analyzed quantitatively using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that both experience quality and loyalty are positively and significantly impacted by existential authenticity. Furthermore, the association between existential authenticity and loyalty is partially mediated by experience quality, which also has a major impact on loyalty. The findings also show that the relationship between experience quality and loyalty is considerably strengthened by trust. These findings indicate that emotionally authentic experiences, immersive festival environments, and trustworthy event management play important roles in encouraging revisit intention and positive word-of-mouth behavior among festival visitors. This study extends the application of the Stimulus–Organism–Response (S-O-R) framework within the context of music festivals and provides practical implications for festival organizers in developing emotionally engaging and sustainable festival experiences that strengthen long-term visitor loyalty.